2021
DOI: 10.1101/2021.05.20.445019
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Decoding the effects of synonymous variants

Abstract: Synonymous single nucleotide variants (sSNVs) are common in the human genome but are often overlooked. However, sSNVs can have significant biological impact and may lead to disease. Existing computational methods for evaluating the effect of sSNVs suffer from the lack of gold-standard training/evaluation data and exhibit over-reliance on sequence conservation signals. We developed synVep (synonymous Variant effect predictor), a machine learning-based method that overcomes both of these limitations. Our trainin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 142 publications
(151 reference statements)
0
1
0
Order By: Relevance
“…Synonymous mutations were previously thought to have no functional impact. Growing studies have shown that synonymous mutations affect DNA, RNA, and protein-based features [23][24][25] . The COL11A2 c.3774 C > T is close to the marginal zone of exons, which does not alter the protein sequence and may cause splicing abnormalities [26] .…”
Section: Discussionmentioning
confidence: 99%
“…Synonymous mutations were previously thought to have no functional impact. Growing studies have shown that synonymous mutations affect DNA, RNA, and protein-based features [23][24][25] . The COL11A2 c.3774 C > T is close to the marginal zone of exons, which does not alter the protein sequence and may cause splicing abnormalities [26] .…”
Section: Discussionmentioning
confidence: 99%